An all‐diamond X‐ray position and flux monitor using nitrogen‐incorporated ultra‐nanocrystalline diamond contacts. (5th June 2018) - Zou, Mengnan; Gaowei, Mengjia; Zhou, Tianyi; Sumant, Anirudha V.; Jaye, Cherno; Fisher, Daniel A.; Bohon, Jen; Smedley, John; Muller, Erik M.
Abstract : Diamond X‐ray detectors with N‐UNCD contacts have been demonstrated for X‐ray flux measurement and position calibration. The contacts have significant advantages over traditional metal contacts due to a lack of extra absorption edges, less absorption in the soft X‐ray range, and similar material properties to the underlying detector material. Abstract : Diamond X‐ray detectors with conducting nitrogen‐incorporated ultra‐nanocrystalline diamond (N‐UNCD) films as electrodes were fabricated to measure X‐ray beam flux and position. Structural characterization and functionality tests were performed for these devices. The N‐UNCD films grown on unseeded diamond substrates were compared with N‐UNCD films grown on a seeded silicon substrate. The feasibility of the N‐UNCD films acting as electrodes for X‐ray detectors was confirmed by the stable performance in a monochromatic X‐ray beam. The fabrication process is able to change the surface status which may influence the signal uniformity under low bias, but this effect can be neglected under full collection bias.